METHODS TO MOTIVATE REMOTE TEACHERS IN A PANDEMIC ENVIRONMENT - Olena Lozova; Olga Bilan; Larysa Novykova; Kateryna Marchenko-Tolsta (International Journal of Innovative Technologies in Social Science, 2021)
The article examines the factors that affect the success of university remote teachers in a pandemic environment, the importance of maintaining the work motivation of teachers to ensure high performance e-learning, and the need for joint efforts by teachers and university administration to prevent professional burnout and maintain a sense of belonging to the team.